Design and Implementation ofReal-time Electrical Stimulation Artifact Suppression based on STM32 - et. al., Sangsoo Park, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A biosignal is used as a control signal for electrical stimulation to restore weakened muscle function due to damage to the central nervous system. In patients with central nervous system damage, sufficient muscle contraction does not occur spontaneously. In this case, applying electrical stimulation can cause normal muscle contraction. However, it is necessary to remove the electrical stimulation artifact caused by the electrical stimulation. This paper describes a system design that removes electrical stimulation artifact in real time using a Cortex-M4-based STM32F processor. The STM32F is a very advantageous MCU for such DSPs, especially because it has a built-in floating point operator. Using STM32F's various high-performance peripherals (12-bit parallel ADC and 12-bit DAC, UART, Timer), an optimized embedded system was implemented.In this paper, the simulated and real-time results were compared and evaluated with the designed fir filter. In addition, the performance of the filter was evaluated through frequency analysis. As a result, it was verified that a high-performance 32-bit STM32F with floating point calculator and various peripherals is suitable for real-time signal processing